Invagination of the small intestine in the adult: small intestine lipoma - Asiner, Boris; Marella, Muzio (Cirugía del Uruguay, 1973)
The author reviews sorne general aspects· of lipomas and invagination of small intestine in adults, such as national case material, patbology, clínica! and radiological aspects, therapy employed and surgical management. He also presents bis own case material consisting of four patients _with pedicled lipoma of small intestine complicated by ileo-ileal and ileo-colic invagination. In one case there was low ileal occlusion, with vascular involvement and mesentero-ileal necrosis. In the remaining three there was jejunal, ileal and ileo-colic invagination. In cases of urgency due to this complication he advises exploratory laparotomy for diagnostica! purposes. The lesion found and its topography will determine surgical procedure employed. When the ileocaecal sector is involved and it is not possible to deinvaginate it, or else there is devitalization, a right ileo-colectomy is indicated. 'I'his will also be the tactic employed when carcinomas cannot be totally discarded. The only safe means, in bis opinion, of establishing the real nature of tumor is through histopathological study, since tumors of similar symptomatology, clinical aspect and topography may or may not be malign.